2021
DOI: 10.3390/ijerph18031368
|View full text |Cite
|
Sign up to set email alerts
|

The Early Detection of Osteoporosis in a Cohort of Healthcare Workers: Is There Room for a Screening Program?

Abstract: Workforce aging is becoming a significant public health problem due to the resulting emergence of age-related diseases, such as osteoporosis. The prevention and early detection of osteoporosis is important to avoid bone fractures and their socio-economic burden. The aim of this study is to evaluate the sustainability of a screening workplace program able to detect workers with osteoporosis. The screening process included a questionnaire-based risk assessment of 1050 healthcare workers followed by measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Increased risk of osteoporosis, tuberculosis, deaths from COVID-19 have been also associated with older HCWs (Lee et al. , 2021; Rinaldi et al. , 2021; Verma et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased risk of osteoporosis, tuberculosis, deaths from COVID-19 have been also associated with older HCWs (Lee et al. , 2021; Rinaldi et al. , 2021; Verma et al.…”
Section: Resultsmentioning
confidence: 99%
“…This study evaluated the association between physical therapists' (PTs) muscular fitness and Work Ability Index (WAI) in Spain and it showed that PTs aged 50 years or older had lower WAI scores than their younger counterparts. Increased risk of osteoporosis, tuberculosis, deaths from COVID-19 have been also associated with older HCWs (Lee et al, 2021;Rinaldi et al, 2021;Verma et al, 2021). Age-related differences were assessed by Merkus et al (2019) and conclusion was made that the level of occupational physical demands and the higher relative physical strain in older employees require addressing to promote sustainable work participation among an ageing population.…”
Section: Health and Lifestylementioning
confidence: 99%
“…Then, when fractures do occur, they can cause serious mobility impairments (Maffulli & Aicale, 2022). In view of the long asymptomatic period, early detection and prevention are essential for minimizing osteoporosis‐related injuries (Rinaldi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing primary prevention would be bene cial-not least to the patient whose fracture risk can be substantially mitigated following diagnosis [9]-but also to the healthcare provider through the reduced cost of treatment prior to fracture [10,11]. One method to increase primary prevention is the IBEX Bone Health (IBEX BH) software, which provides a measure of aBMD and T-score at the ultra-distal (UD) and distal-third (TD) regions [12,13] from standard digital radiographs (DRs) of the forearm.…”
Section: Introductionmentioning
confidence: 99%